Beyond Words: The Psychological and Physiological Impacts of English Language Anxiety in Medical Education - Salimi Chegenie, Milad (Novelty in Biomedicine, 2026)
Background: English has become the primary medium of instruction in medical education, creating linguistic and psychological challenges for non-native speakers. English language learning anxiety may affect both mental health and sleep quality, yet its impact in medical students remains underexplored. This study examined the relationships among English learning anxiety, generalized anxiety, and sleep quality. Materials and Methods: A cross-sectional survey was conducted with 286 medical students enrolled in English-medium programs. Participants completed the Medical English Language Anxiety Scale (MELAS), Generalized Anxiety Disorder-7 (GAD-7), and Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using descriptive statistics, correlations, and multiple regression analyses. Results: Moderate-to-high English learning anxiety was reported by 72.4% of students, and 61.5% experienced poor sleep quality. English learning anxiety correlated positively with generalized anxiety (r = 0.48, p < 0.001) and sleep disturbance (r = 0.42, p < 0.001). Regression analyses indicated that language anxiety independently predicted poorer sleep quality, and generalized anxiety partially mediated this relationship. Conclusion: English language learning anxiety is a significant psychological burden for medical students, affecting both anxiety levels and sleep quality. Integrating language anxiety management and psychological support into medical English curricula may improve students’ well-being and academic performance.